Pengimbasan Literatur: Jalan Dan Rekabentuknya Dalam Konteks Bandar - Elina Mohd Husini; Fadli Arabi; Nor Haslina Ja’afar; Ismar M. S. Usman; Mohd Iskandar Malek (Jabatan Seni Bina Universiti Kebangsaan Malaysia, 2024)
Indexed by MyCite